Exploring Teachers’ Pedagogical Practices of Flipped Learning in Indonesian EFL Reading Instruction - Rahayuningsih, Retno; Hartono, Rudi; Pratama, Hendi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study explores the pedagogical practice of EFL Indonesia lecturers in applying Flipped Learning (FL) to reading teaching. Through a qualitative approach with a descriptive design, data were collected from Likert scale questionnaires (N=30) and structured interviews (N=5) with lecturers from various universities. The findings revealed that although lecturers showed high conceptual readiness in designing FL-based lesson plans score 4.40 (88%), the practice of designing pre-class materials varied widely, ranging from the use of multimodal (66%), the inclusion of question guides (21%), to the reliance on simple videos (7%) or textbooks (6%) due to time and infrastructure constraints. In the implementation phase, class activities were dominated by collaborative interaction with a score of 4.71 (94.29%). However, the transition of the role of lecturers from material presenters to facilitators was still a big challenge, with a score of 2.71 (54.29%). Practical reflection was also not systematic, although lecturers evaluated and improved the strategy with a score of 4.00 (80%). The study concludes that the success of FL depends not only on technical readiness but also on ongoing pedagogical support through interactive material design training, facilitator role mentoring, and institutional policies that provide resources and low-tech solutions. This research contributes to the literature by highlighting the teacher's perspective and the contextualization of FL in Indonesian settings.